2014
DOI: 10.1080/13557858.2014.907389
|View full text |Cite|
|
Sign up to set email alerts
|

Perceived discrimination, humiliation, and mental health: a mixed-methods study among Haitian migrants in the Dominican Republic

Abstract: Both qualitative and quantitative methods suggest that perceived discrimination and the experience of humiliation contribute to Haitian migrant mental ill-health and limit access to health care. Future research should evaluate these associations and identify intervention pathways for both improved treatment access and reduction of discrimination-related health risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 41 publications
1
29
0
12
Order By: Relevance
“…Increasingly, migrants within the Americas are foregoing the United States and Canada as destinations in favor of movement between Latin American states (IOM 2012). About half of all migrants are women (Basok and Piper 2012), and depending on the geographic context, many are undocumented (Keys et al 2014). Formal economic opportunities for undocumented women in Latin America are limited and often pay little, such as domestic work.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, migrants within the Americas are foregoing the United States and Canada as destinations in favor of movement between Latin American states (IOM 2012). About half of all migrants are women (Basok and Piper 2012), and depending on the geographic context, many are undocumented (Keys et al 2014). Formal economic opportunities for undocumented women in Latin America are limited and often pay little, such as domestic work.…”
Section: Introductionmentioning
confidence: 99%
“…Os 17 artigos científicos revisados por pares e incluídos na revisão foram publicados e realizados nos EUA e República Dominicana, entre os anos de 2009 a 2017, em revistas especializadas, com publicação máxima de três artigos nos anos de 2012 e 2014. No que se refere à autoria dos artigos, a maioria dos estudos possui autoria múltipla entre dois a oito autores [32][33][34][35][36][37][38][39][40][41][42][43][44][45] . Os pesquisadores que se destacaram com maior número de publicações foram: Marie-Anne Sanon, primeira autora em três trabalhos 33,37,46 ; Erin Kobetz, primeiro autor em dois trabalhos 42,43 e coautor em outros três 21,40,44 ; e Janelle Menard, primeira autora em dois artigos 40,44 e coautora em outros três 21,42,43 .…”
Section: Resultados Análise Bibliométricaunclassified
“…Somente dois estudos mistos foram incluídos, um realizado na Flórida 40 e outro, na República Dominicana 41 . Com relação aos conceitos e perspectivas teórico-metodológicas, observou-se que oito trabalhos não delimitam uma abordagem específica 34,35,38,39,41,42,44,45 .…”
Section: Resultados Análise Bibliométricaunclassified
See 1 more Smart Citation
“…Studies have found variations in the association between health and discrimination in different population groups [1,2,[18][19][20][21][22][23][24]. These inconsistencies in the association between discrimination and health may be due to the different populations and health measures used in the studies [25].…”
Section: Introductionmentioning
confidence: 92%